Discovery Process Chemistry: An Innovation Hub at the Interface of Academia, the Pharmaceutical Industry, and Contract Research Organizations - Horwitz, Matthew A. (Synthesis, 2024)
Discovery Process Chemistry (DPC) is an emerging intersectoral space that is characterized by the development of new chemical reactions or syntheses that enable the efficient elucidation of structure-activity relationships (SARs) and structure-property relationships (SPRs) as well as a rapid transition to process development. Drug discovery and development are accelerated by such efforts and this has led chemists in academia and industry alike to place an increasing importance on these aims. In this Short Review, we explore recent advances in DPC and the impact that it can have on SAR/SPR interrogation and downstream drug development efforts.1 Introduction2 Enabling SAR/SPR Interrogation with Bioisosteres3 Couplings of Diversifiable Reaction Partners4 Late-Stage Functionalization5 Conclusion and Outlook
Keywords: discovery process chemistry; late-stage functionalization; SAR/SPR exploration; diversity-oriented synthesis; route scouting and process development